Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1016/j.respol.2010.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with disciplinary and interdisciplinary research collaboration

Abstract: There is a lack of understanding regarding the optimal conditions for interdisciplinary research. This study investigates what characteristics of researchers are associated with disciplinary and interdisciplinary research collaborations and what collaborations are most rewarding in different scientific disciplines. Our results confirm that female scientists are more engaged in interdisciplinary research collaborations. Further, a scientist's years of research experience are positively related with both types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
202
2
12

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 346 publications
(237 citation statements)
references
References 56 publications
7
202
2
12
Order By: Relevance
“…Therefore, there is a potential risk of non-response bias in some countries. However, national samples were found broadly representative of the respective populations on strata such as gender, academic rank and institutional type (Cummings and Finkelstein 2012;RIHE 2008;Vabø and Ramberg 2009). Further, there are few reasons to expect that nonrespondents would differ substantially in terms of self-declared research orientation.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, there is a potential risk of non-response bias in some countries. However, national samples were found broadly representative of the respective populations on strata such as gender, academic rank and institutional type (Cummings and Finkelstein 2012;RIHE 2008;Vabø and Ramberg 2009). Further, there are few reasons to expect that nonrespondents would differ substantially in terms of self-declared research orientation.…”
Section: Methodsmentioning
confidence: 99%
“…6,50 Research suggests, however, that women are more likely than men to participate in interdisciplinary, collaborative research. 51,52 In addition, women are more likely than men to consider perceived quality of life, earnings potential, and organizational reward; they are less likely than men to identify role models for personal-professional balance or to identify recognition as a national leader as motivating. 53 A Johns Hopkins follow-up study of women faculty who left the institution identified themes that influenced their decisions to leave.…”
Section: Individual Choices and Decisions: Aligning Values And Responmentioning
confidence: 99%
“…This is because collaboration across knowledge domains is recognized as a source of competitive advantage (Liedtka, 1999;Scarbrough and Swan, 2008) and a response to the complex demands of the modern world (Aram, 2004;Buanes and Jentoft, 2009;Huutoniemi et al, 2010;König et al, 2013;van Rijnsoever and Hessels, 2011). Nevertheless a gap exists in our knowledge of how such collaborations are accomplished and the kinds of emergent organizational forms in which it occurs.…”
Section: Introductionmentioning
confidence: 99%